SYEKH MUHCSIN DAN KIPRAHNYA MENGEMBANGKAN TAREKAT SYATTARIYAH DI SOLOK ABAD KE 17-18 M - Nurvela Hayati (Hadharah: Jurnal Keislaman dan Peradaban, 2021)
The focus of this study is on Sheikh Muchsin's efforts in a variety of disciplines, including establishing the Syattariyah congregation's teachings in Solok, which comprise science such as Fiqh, Hadith, Nahwu, and Sufism. Sheikh Muchsin's role in the construction of the Sijunjuang hamlet and the establishment of the Lubuk Sikarah mosque in Solok. Sheikh Muchsin was one of the first intellectuals to contribute to the development of Islam in Solok; he extended Islam from Solok to Sijunjuang and remained prominent after his time. Because this topic has not been written on by other scholars, the author is interested in bringing it up. Sheikh Muchsin is associated with the history of early Islam in Solok. The problem is related to time to the 17th and 18th centuries AD since Sheikh Muchsin conducted da'wah efforts and participated in the Syattariyah assembly in Solok to Sijunjung during this period. Because he propagated Islam in Solok and the surrounding areas, the research's spatial constraint is Solok and its environs. The purpose of this research is to uncover the history of early Islam in Minangkabau, to uncover the history of early Islam in Solok, to uncover Sheikh Muchsin's life story, to evaluate Sheikh Muchsin's approach to establishing Syattariyah teachings in Solok, and to uncover Sheikh Muchsin's writings. This study's methodology focuses on the historical element, namely on Sheikh Muchsin's history and contributions to the development of the Syattariyah order in Solok. And this research project is an investigation of Intellectual History. The writer gathers this facts from written, oral, and observational sources.